Seed-transmission of Cowpea mild mottle virus on several varieties of soybean in Indonesia - Mimi Sutrawati; Sri Hendrastuti Hidayat; Gede Suastika; Bonny Purnomo Wahyu Sukarno; Ali Nurmansyah (Society for Indonesian Biodiversity, 2021)
Abstract. Sutrawati M, Hidayat SH, Suastika G, Sukarno BPW, Nurmansyah A. 2021. Seed-transmission of Cowpea mild mottle virus on several varieties of soybean in Indonesia. Biodiversitas 22: 4182-4185. Seeds and infected plants play important role as source of disease in the field for seed-transmitted virus, such as Cowpea mild mottle virus (CPMMV). Research was conducted to determine seed transmission nature of CPMMV on 10 soybean varieties based on growing on test method and dot immunobinding assay to confirm CPMMV infection. Field experiment was conducted to evaluate the efficiency of seed-transmitted CPMMV as the source of initial inoculum in the field. Soybean var. ‘Anjasmoro’ from 3 cultivation areas (Cianjur, Bogor, and Cirebon) was used for field experiment. Seed transmission of CPMMV was confirmed on soybean var. ‘Detam 2’, ‘Detam 3’, ‘Malika’, ‘Anjasmoro’, and ‘Argomulyo’; but was not found on ‘Detam 1’, ‘Detam 4’, ‘Wilis’, ‘Grobogan’, and ‘Dena 1’. The infection of CPMMV did not show symptom, either on the seedcoat and the unifoliolate leaves. Infection rate of CPMMV on seeds were relatively high, ranged between 27 to 86%. Disease incidence on var. ‘Anjasmoro’ from Cianjur, Cirebon, and Bogor varied from 32.9 to 75% and 57.9 to 81.3% in screenhouse and field experiment, respectivelly.